Stroke care and collaborative academic research in Latin America - Paula Muñoz-Venturelli; Francisca González; Francisca Urrutia; Enrico Mazzon; Victor Navia; Alejandro Brunser; Pablo Lavados; Verónica Olavarría; Juan Almeida; Rodrigo Guerrero; Alexis Rojo; Juan Pablo Gigoux; et al. (Instituto Nacional de Salud Pública, 2022)
Objective. A narrative overview of regional academic research collaborations to address the increasing burden and gaps in care for patients at risk of, and who suffer from, stroke in Latin America (LA). Materials and methods. A summary of experiences and knowledge of the local situation is presented. No systematic literature review was performed. Results. The rapidly increasing burden of stroke poses immense challenges in LA, where prevention and management strategies are highly uneven and inadequate. Clinical research is increasing through various academic consortia and networks formed to overcome structural, funding and skill barriers. However, strengthening the ability to generate, analyze and interpret randomized evidence is central to further develop effective therapies and healthcare systems in LA. Conclusions. Regional networks foster the conduct of multicenter studies -particularly randomized controlled trials-, even in resource-poor regions. They also contribute to the external validity of international studies and strengthen systems of care, clinical skills, critical thinking, and international knowledge exchange.